Synergy model and financial bookkeeping administration through technopreneurship education: does it impact on increasing the competitiveness of MSMES? - Andi Arifwangsa Adiningrat; Andi Rustam; Arniati Arniati; Warda Warda; Naidah Naidah (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2024)
This synergy model refers to collaboration between technology and business expertise in the context of technopreneurship education. A modern approach through technopreneurship education can help MSMEs adopt an effective financial bookkeeping system, including the use of technology in carrying. This research aims to determine and analyze the synergy and administration model of financial bookkeeping through technopreneurship education which has an impact on increasing the competitiveness of Micro, Small and Medium Enterprises (MSMEs). This research was carried out at the Culinary Food MSMEs located in Gowa Regency and Makassar City, South Sulawesi Province. The data analysis method in this research uses qualitative data analysis. This research method aims to get general answers about cause and effect by analyzing the factors that cause phenomena in the concepts raised in this research. Data collection was carried out by distributing questionnaires and interviews with informants from Micro, Small and Medium Enterprises (MSMEs). The steps in qualitative analysis techniques start from data reduction, data presentation and drawing conclusions. The research results show that the synergy model that was designed has a positive impact, but the synergy model through technopreneurship education is less effective in being implemented by MSMEs so that the competitiveness of MSMEs is not optimal. Apart from that, MSMEs tend to carry out financial administration manually and irregularly so that bookkeeping administration through technopreneurship does not have an impact on increasing competitiveness. Meanwhile, technopreneurship education is very useful and has an impact, but the competitiveness of MSMEs has not fully increased.